Field observations on Takecallis arundinariae (Essig) and T. taiwanus (Takahashi) (Bollettino di zoologia agraria e bachicoltura, 2024)
Takecallis arundinariae and T. taiwanus are the most widespreadaphids in bamboo nurseries in Lombardy. Field observations were carried out onPhyllostachis bambusoides on different stages and on mean fecundity; seasonalabundance has been studied for three years. T. arundinariae youngs has a meanlife of 7,3 days, nymphs of 4,9 and adults of 62,4. The reproductive period lasts57,5 days and fecundity is 151,4 youngs per female. T. taiwanus youngs has amean life of 10,7 days, nymphs of 4,9 and adults of 65,8. The reproductive periodlasts 61,7 days and fecundity is 105,7 youngs per female. The first species developsfrom February to the end of May, the second one from the beginning of Mayto the first days of August.
Keywords: Takecallis arundinariae; T. taiwanus; Phyllostachys bambusoides; fecundity; aphid bionomics